2021
DOI: 10.1007/s00395-021-00863-x
|View full text |Cite
|
Sign up to set email alerts
|

Cytokines as therapeutic targets for cardio- and cerebrovascular diseases

Abstract: Despite major advances in prevention and treatment, cardiac and cerebral atherothrombotic complications still account for substantial morbidity and mortality worldwide. In this context, inflammation is involved in the chronic process leading atherosclerotic plaque formation and its complications, as well as in the maladaptive response to acute ischemic events. For this reason, modulation of inflammation is nowadays seen as a promising therapeutic strategy to counteract the burden of cardio- and cerebrovascular… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
42
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(43 citation statements)
references
References 254 publications
(264 reference statements)
0
42
0
1
Order By: Relevance
“…Cardiovascular diseases: hypertension, dyslipidemia, coronary heart disease, and heart insufficiency are among the main causes of death in the world [ 82 ]. A soy-rich diet (at least 25 g of soy protein daily) has been shown to reduce the risk of cardiovascular diseases [ 83 , 84 , 85 ].…”
Section: The Role Of Isoflavones In Chronic Degenerative Diseasesmentioning
confidence: 99%
“…Cardiovascular diseases: hypertension, dyslipidemia, coronary heart disease, and heart insufficiency are among the main causes of death in the world [ 82 ]. A soy-rich diet (at least 25 g of soy protein daily) has been shown to reduce the risk of cardiovascular diseases [ 83 , 84 , 85 ].…”
Section: The Role Of Isoflavones In Chronic Degenerative Diseasesmentioning
confidence: 99%
“…Though not direct evidence for ILCs in MIRI, several groups (22,(41)(42)(43) have reported roles for ILCs in IRI and ILC-related cytokines in MIRI, suggesting that ILCs can play important roles in MIRI, with ILC2s being the most promising candidate.…”
Section: Discussion and Prospectsmentioning
confidence: 99%
“…( 43 ) summarized the multifactorial and dynamic process of the inflammatory response in MIRI, including TNF-α, IL-4, IL-13, IL-10 and TGF-β. These results suggested that cytokines, especially those related to ILCs, play important roles in MIRI ( 22 ).…”
Section: The Role Of Ilcs In Myocardial Ischemia-reperfusion Injurymentioning
confidence: 92%
See 1 more Smart Citation
“…Inflammation is a central process in the development and destabilisation of atherosclerotic plaques, leading to serious cardiovascular events such as myocardial infarction and Nutrients 2021, 13, 3047. https://doi.org/10.3390/nu13093047 https://www.mdpi.com/journal/nutrients Nutrients 2021, 13, 3047 2 of 16 stroke [1][2][3]. A number of chemokines is involved in the complex process of atherosclerotic plaque formation to recruit of various leukocytes, such as monocytes, macrophages and T lymphocytes, to the site of developing atheroma [4].…”
Section: Introductionmentioning
confidence: 99%